Terracotta statuetties from the Great Guldursun settlement: art and social processes of the Right Bank Khorezm - Dospanov, Oktyabr T.; Boymirzaev, Sarvar B.; Sаfаеv, Mаnsur M. (Journal of the Belarusian State University. History, 2026)
This article examines the origins of terracotta statuetties from the Great Guldursun settlement (Khorezm) as a key element in the study of the region’s socio-economic and cultural-historical ties with neighboring countries. The focus is on the largely unexplored terracotta statuetties, which represent unique artifacts reflecting the artistic traditions and social processes of Khorezm. The significance of these statuetties in cultural and trade interactions, as well as in understanding changes in the region’s social structure, is analysed. It emphasises that the artistic specificity of terracotta artifacts remains insufficiently studied, opening new horizons for further research. New information about the urban and political structure of Khorezm is revealed, contributing to the enrichment of existing knowledge about the region’s cultural heritage.
Keywords: Khorezm; terracotta; Great Guldursun; art museum; monkey; archaeological finds; historical and cultural connections